MEMBANGUN KARAKTER RELIGIUS SISWA MELALUI PEMBELAJARAN MEMBACA DAN MENGHAFAL AL-QURAN : DITINJAU DARI PERAN SEKOLAH DAN ORANG TUA SISWA - Mahrus As’ad (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to determine how religious character is, learning tahfidz, programs for strengthening religious characters by learning tahsin and tahfidz in elementary schools, and the role of parents in shaping religious character. This research method is a qualitative descriptive study whose data were obtained from observations, questionnaires through the distribution of google forms in December 2021, and interviews. The objects of this research are parents and teachers of first and second grades of an Islamic Elementary School in Bandung Regency. Data processing with the help of SPSS version 23 to see descriptive statistical crosstab data. The results of the study were obtained as follows: Learning to read and memorize the Koran (tahsin and tahfidz) using the MAQDIS method through three activity programs. The role of parents in building children's religious character consists of affective indicators, cognitive indicators, conation indicators, faith indicators, and charity indicators. More than half of parents play a role in activities that can build children's religious character through: habituation of prayer, reciting and memorizing the Qur'an, speaking well and politely, and four towards others. One of the roles of schools is the tahsin and tahfidz programs which are carried out consistently every day.